COST ANALYSIS FOR HOSPITALS. - Rorem, C. Rufus (The Accounting Review, 1930)
Abstract The purposes and methods of cost analysis which may be applied to hospitals are similar to those which are encountered in business enterprise. It is sometimes assumed that the output of a hospital is homogeneous, that all patients receive essentially the same type of service except for the external features, such as room furnishings, selection of food, amounting of nursing acre, and type of medical or surgical attention. But the activities of a modern hospital are varied in character, even in the care of in-patients. In-patients may receive three general classes of service which ordinarily are charged against the patient's account as separate items. These three classes of revenue producing services are board and room, diagnosis, and treatment. Board and room includes the use of a bedroom, three meals per day, and a reasonable amount of bedside nursing care. Diagnosis includes the services of X-ray photography, basal metabolism, laboratory tests, etc. Medical treatment includes the use of such facilities as the operating room, physiotherapy delivery room, etc. None of these services include, of course, the advice and treatment by a private physician or surgeon.